WeCare Project: Development of Web-based Platform for Online Psychological Consultation using Scrum Framework - Frisca Febriyani Kurniawan; Fauzan Radifan Shidiq; Edi Sutoyo (Bulletin of Computer Science and Electrical Engineering, 2020)
Symptoms and signs of mental disorders depend on the type of disorder experienced. Patients can experience interference with emotions, thought patterns, and behavior. Ways to determine the diagnosis and check whether you have a mental illness, there are several ways in the form of physical examination through a doctor, laboratory tests, psychological evaluation. There is also therapy as a healing process and recovery of the soul that is healthy. In Indonesia, many people experience mental health problems, but most are not aware of and care about these problems. Even in the worst cases, many cases lead to suicide. One factor that triggers suicide is, people who experience mental health problems do not have a place to talk about the problems they are facing, because in each city itself not all the availability of psychologist services that can help sufferers of mental health problems, let alone remember the price of psychologist services offered is quite expensive. Therefore, by taking into account these considerations, the WeCare project proposes developing a web-based platform for online psychologist consultation. In general, this platform has three main actors namely, admin, user, and psychologist. This platform is expected to be a media liaison between users (patients) with psychologists in conducting consultations.